2019
DOI: 10.1002/ece3.5618
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure, migration, and polyploidy origin of a medicinal species Gynostemma pentaphyllum (Cucurbitaceae)

Abstract: Gynostemma pentaphyllum, a member of family Cucurbitaceae, is a perennial creeping herb used as a traditional medicinal plant in China. In this study, six polymorphic nSSR and four EST‐SSR primers were used to genotype 1,020 individuals in 72 wild populations of G. pentaphyllum. The genetic diversity and population structure were investigated, and ecological niche modeling was performed to reveal the evolution and demographic history of its natural populations. The results show that G. pentaphyllum has a low l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 94 publications
2
21
0
Order By: Relevance
“…Currently, transcriptome derived SSR markers have been widely applied in population genetic analyses of medicinal plants, such as Picria felterrae ( Yan et al, 2019 ), Gynostemma pentaphyllum ( Zhang et al, 2019 ), and Perilla frutescens ( Sa et al, 2018 ). Researches on constructing core collections of medicinal plants using transcriptome derived SSRs are also quickly increased in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, transcriptome derived SSR markers have been widely applied in population genetic analyses of medicinal plants, such as Picria felterrae ( Yan et al, 2019 ), Gynostemma pentaphyllum ( Zhang et al, 2019 ), and Perilla frutescens ( Sa et al, 2018 ). Researches on constructing core collections of medicinal plants using transcriptome derived SSRs are also quickly increased in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…It can be found as a health supplement in beverages, biscuits, face washes, and bath oils (Li et al, 2016). The herb has a low level of genetic diversity and a high level of variation among populations (Zhang et al, 2019).…”
Section: Gynostemma Pentaphyllummentioning
confidence: 99%
“…Hence, the high F ST (0.596) and the low gene flow (0.346) found in this study contributed to the observed genetic structure, supported by significant IBD patterns in the study area (r = 0.448, P = 0.004). Zhang et al (2019) submitted that asexual propagation would also reduce genetic differences among individuals within populations and increase differences among populations.…”
Section: Population Genetic Structurementioning
confidence: 99%